2009
DOI: 10.1021/am900023j
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Fundamental Chemical Nature of Ionic Liquid Film Formation on Magnesium Alloy Surfaces

Abstract: Ionic liquids (ILs) based on trihexyltetradecylphosphonium coupled with either diphenylphosphate or bis(trifluoromethanesulfonyl)amide have been shown to react with magnesium alloy surfaces, leading to the formation a surface film that can improve the corrosion resistance of the alloy. The morphology and microstructure of the magnesium surface seems critical in determining the nature of the interphase, with grain boundary phases and intermetallics within the grain, rich in zirconium and zinc, showing almost no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 31 publications
4
87
0
6
Order By: Relevance
“…47 However, other studies using ToF-SIMS revealed that both the cation and anion are present in the film although only the cation could be identified as a whole molecule. 26 This confirms that the anion reactivity plays a dominant role in the passivation of aluminium current collectors whilst the cation is somehow entrapped within the passive surface film.…”
Section: Sem and Edxs Studiesmentioning
confidence: 94%
“…47 However, other studies using ToF-SIMS revealed that both the cation and anion are present in the film although only the cation could be identified as a whole molecule. 26 This confirms that the anion reactivity plays a dominant role in the passivation of aluminium current collectors whilst the cation is somehow entrapped within the passive surface film.…”
Section: Sem and Edxs Studiesmentioning
confidence: 94%
“…As in the cases of Mg and AZ31, the ZE41 surface showed no change in appearance following exposure to the ionic liquid; however, unlike those cases, where samples subjected to long-term exposure led to thick deposits, visible via SEM analysis, SEM analysis of the ZE41 substrate showed no features indicative of film formation [81]. Conversely, EIS obtained during a 24-h treatment of the ZE41 coupon revealed rapid buildup of a resistive component on the surface, during which time the OCP showed extensive noise, indicative of an ongoing electrochemical process likely occurring on the surface, both indicating likely film formation.…”
Section: Fluoride Conversion Treatment [Bis(trifluoromethanesulfonyl)mentioning
confidence: 78%
“…Another pretreatment option lies in the replacement of the oxide/hydroxide layer either as a companion for, or substitute to, further deposition. The continued research into batteries, especially lithium batteries [77,78], has produced several new insights into the potential of ionic liquids, including their use as a surface conversion treatment on magnesium [79][80][81], and research into the lubrication properties of ionic liquids in wear minimization have found that the same ILs are also able to produce beneficial tribological surface layers, in part due to their dipolar structure, in aluminum-steel interfaces [82][83][84][85].…”
Section: Ionic Liquids and Surface Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorus-containing ionic liquids have been extensively applied in corrosion protection of magnesium alloys [55][56][57][58][59][60][61][62][63][64]. Together with corrosion, another major cause of surface failure of magnesium alloys is their poor tribological performance.…”
Section: Introductionmentioning
confidence: 99%